Phylogeographical Variation of Chloroplast DNA in Cork Oak (Quercus suber) (Annals of Botany)
• Background and Aims In the last decades, the geographical location of the centre of origin of Quercus suber (cork oak), a strictly western Mediterranean oak species, has been the subject of controversy.• Methods RFLP variation over the whole chloroplast DNA molecule and PCR–RFLPs over seven specific cpDNA fragments were analysed phylogeographically to reconstruct the evolutionary history of cork oak.• Key Results Nine chlorotypes of the ‘suber’ cpDNA lineage were identified throughout the species range. Using closely related Mediterranean oak species as outgroup, the chlorotypes showed a clear phylogeographical pattern of three groups corresponding to potential glacial refuges in Italy, North Africa and Iberia. The most ancestral and recent groups were observed in populations located in the eastern and western parts of the species range, respectively. Several unrelated chlorotypes of the ‘ilex’ cpDNA lineage were also identified in specific western areas.• Conclusions The results support a Middle-Eastern or a central Mediterranean origin for cork oak with subsequent westward colonization during the Tertiary Period, and suggest that the ‘ilex’ chlorotype variation does not reflect entirely cytoplasmic introgression by Q. ilex but originated partly in Q. suber.
10.1093/aob/mci237

The diversification of terpene emissions in Mediterranean oaks: lessons from a study of Quercus suber, Quercus canariensis and its hybrid Quercus afares - Welter, Saskia; Bracho-Nuñez, Araceli; Mir, Celine; Zimmer, Ina; Kesselmeier, Jürgen; Lumaret, Roselyne; Schnitzler, Jörg-Peter; Staudt, Michael (Tree Physiology, 2012)
Interspecific gene flow is common in oaks. In the Mediterranean, this process produced geographical differentiations and new species, which may have contributed to the diversification of the production of volatile terpenes in the oak species of this region. The endemic North African deciduous oak Quercus afares (Pomel) is considered to be a stabilized hybrid between the evergreen Quercus suber (L.) and the deciduous Quercus canariensis (Willd.), presumably being monoterpene and isoprene emitters, respectively. In a common garden experiment, we examined the terpene emission capacities, terpene synthase (TPS) activities and nuclear genetic markers in 52 trees of these three oak species. All but one of the Q. suber and Q. canariensis trees were found to be genetically pure, whereas most Q. afares trees possessed a mixed genotype with a predominance of Q. suber alleles. Analysis of the foliar terpene emissions and TPS activities revealed that all the Q. canariensis trees strongly produced isoprene while all the Q. suber trees were strong monoterpene producers. Quercus afares trees produced monoterpenes as well but at more variable and significantly lower rates, and with a monoterpene pattern different than that observed in Q. suber. Among 17 individuals tested, one Q. afares tree emitted only an insignificant amount of terpenes. No mixed isoprene/monoterpene emitter was detected. Our results suggest that the capacity and pattern of volatile terpene production in Algerian Q. afares populations have strongly diverged from those of its parental species and became quantitatively and qualitatively reduced, including the complete suppression of isoprene production.
10.1093/treephys/tps06910.1093/treephys/tps069
Keywords: Algerian oak; allozyme polymorphism; chemo-taxonomy; chemotype; Cork oak; isoprene synthase; isoprenoid; speciation

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression - Staudt, Michael; Mir, Celine; Joffre, Richard; Rambal, Serge; Bonin, Aurelie; Landais, Damien; Lumaret, Roselyne (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.
Keywords: basal emission rate; chemotaxonomy; chemotypes; Evergreen oaks; genetic introgression; isoprene; Monoterpenes; VOC (volatile organic compound) emissions.